Effect of fish oil-derived omega-3 polyunsaturated fatty acid supplementation on exercise-induced bronchoconstriction and immune function in athletes - Mickleborough, T. D.; Lindley, M. R.; Montgomery, G. S. (The Physician and Sportsmedicine, 2008)
Abstract: Exercise-induced bronchoconstriction (EIB) is a condition in which vigorous physical activity triggers acute airway obstruction in asthmatic and nonasthmatic individuals with hyperresponsive airways. Studies have shown that inflammatory mediators and contraction of airway smooth muscle are central components in the pathogenesis of EIB, and it has long been recognized that leukotrienes and prostaglandins play an important role in the EIB response. Clinical responses to current therapy, such as leukotriene modifiers and corticosteroids are heterogeneous, and even with optimal treatment there is a substantial burden of unaddressed disease. While daily medications such as leukotriene modifiers provide only modest protection against symptoms, prolonged use of several medications can result in reduced effectiveness or tachyphylaxis. Although the treatment of EIB almost exclusively involves pharmacotherapy, there is now convincing evidence that dietary modification has the potential to reduce the severity of this condition. Omega-3 polyunsaturated fatty acids, such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in fish oils, compete with arachidonic acid as substrates for the formation of proinflammatory mediators, such as leukotrienes, prostaglandins, and cytokines. Studies have shown that 3 weeks of fish oil supplementation, rich in EPA and DHA, reduces exercise-induced airway narrowing, airway inflammation, and bronchodilator use in elite athletes and asthmatic individuals with EIB. Based on the evidence to date, fish oil supplementation may represent a potentially beneficial treatment intervention for athletes and asthmatic individuals with EIB. From this, it follows that physicians should pay more attention to what their asthma/EIB patients eat, and incorporate dietary assessment and nutritional counseling in their everyday practice.